UJI AKTIVITAS ANTIOKSIDAN DAN PENENTUAN NILAI SPF SECARA IN VITRO EKSTRAK KULIT BUAH RAMBUTAN (Nephelium lappaceum), MANGGIS (Garcinia mangostana) DAN DURIAN (Durio zibethinus) - Yola Desnera Putri; Deby Tristiyanti; Aneu Nurdiana (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACTRambutan rind, mangosteen rind, and durian rind contain phenolic compoundsand flavonoids that have high antioxidant activity, also thought to be efficaciousas a sunscreen. The aims of this research was to determined the antioxidantactivity and the SPF of sunscreen ethanol extract of mangosteen rind (Garciniamangostana), rambutans rind (Nephelium lappaceum) and durian rind (Duriozibethinus). The extraction method was used maceration method using ethanol96%. DPPH (1, 1- diphenyl-2-picrylhidrazil) was used to determine theantioxidant activity. The effectiveness of sunscreen was done by determine theSPF value in vitro using spectrophotometric method. The results showed that thethree ethanol extracts containing phenolic compounds and flavonoids. Thosecompounds have antioxidant activity and also sunscreen, the highest antioxidantactivity owned by ethanol extracts of rambutan rind with the value IC50 amountingto 2,697 ppm, second are ethanol extracts of mangosteen rind with IC50amounting to 2,710 ppm and lastly, ethanol extracts of durian rind with the valueIC50 amounted to 11.398 ppm, whereas for the highest SPF value owned by theethanol extract of mangosteen rind 29.008, then ethanol extract rind of rambutansat 9.99. Both of ethanol extract rinds have a high antioxidant activity andpotential to be used as active ingredients in sunscreen preparations, while toextract durian rind ethanol does not have the ability as sunscreen because theSPF value was 0.967.Keywords : Garcinia mangostana, Nephelium lappaceum, Durio zibethinus,antioxidant, sunscreen